Two-particle transverse momentum correlations in pp and p-Pb collisions at energies available at the CERN Large Hadron Collider - Acharya, Shreyasi; Berdnikova, Anastasia; Bergmann, Luisa; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kim, Jiyoung; Kroesen, Martin; López, Jorge; Nath, Abhishek; et al. (Physical review, 2023)
Two-particle transverse momentum differential correlators, recently measured in Pb-Pb collisions at energies available at the CERN Large Hadron Collider (LHC), provide an additional tool to gain insights into particle production mechanisms and infer transport properties, such as the ratio of shear viscosity to entropy density, of the medium created in Pb-Pb collisions. The longitudinal long-range correlations and the large azimuthal anisotropy measured at low transverse momenta in small collision systems, namely 𝑝⁢𝑝 and 𝑝-Pb, at LHC energies resemble manifestations of collective behavior. This suggests that locally equilibrated matter may be produced in these small collision systems, similar to what is observed in Pb-Pb collisions. In this work, the same two-particle transverse momentum differential correlators are exploited in 𝑝⁢𝑝 and 𝑝-Pb collisions at √𝑠=7TeV and √𝑠𝑁⁢𝑁=5.02TeV, respectively, to seek evidence for viscous effects. Specifically, the strength and shape of the correlators are studied as a function of the produced particle multiplicity to identify evidence for longitudinal broadening that might reveal the presence of viscous effects in these smaller systems. The measured correlators and their evolution from 𝑝⁢𝑝 and 𝑝-Pb to Pb-Pb collisions are additionally compared to predictions from Monte Carlo event generators, and the potential presence of viscous effects is discussed.